THE EFFECTIVENESS OF INQUIRY LESSON-BASED IMMUNITY SYSTEM MODULE TO EMPOWER THE STUDENTS’ CRITICAL THINKING SKILL - Evi Elisanti; Sajidan Sajidan; Baskoro Adi Prayitno (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
EFEKTIFITAS MODUL SISTEM IMUNITAS BERBASIS PEMBELAJARAN INQUIRY DALAM MEMEBERDAYAKAN KETRAMPILAN PEMIKIRAN KRITIS SISWA AbstractThis research aimed to find out the effectiveness of inquiry lesson (IL)-based immunity system module product to empower the students’ critical thinking skill. This study was quasi-experimental research with pretest-posttest control group design nonequivalent. The participant or subject of research consisted of 67 Senior High School students in Kediri in Academic Year of 2016/2017 distributed in two classes: 33 students in the 11th Natural Science 2 Grade as experiment class and 34 students in the 11th Natural Science 3 Grade as existing class. The instrument used to collect data on critical thinking skill was essay test. Experiment class was treated using inquiry lesson-based module, and existing class using module commonly used at school. Data analysis employed t-test at significance level with p-value = 0.000 (p<0.05). The gap between pre- and posttest scores was 20.99% for experiment class and 10.76% for existing class. From the result of research, it could be concluded that learning using inquiry lesson (IL)-based immunity system in learning process is very significant to empower the students’ critical thinking skill.AbstrakPenelitian ini bertujuan untuk mengetahui keefektifan produk modul sistem imunitas berbasis inquiry lesson (IL) untuk memberdayakan keterampilan berpikir kritis siswa. Penelitian ini merupakan penelitian kuasi-eksperimental dengan pretest-posttest control group design nonequivalent. Partisipan subjek penelitian dilakukan di salah satu Sekolah Menengah Atas di Kediri tahun Akademik 2016/2017 berjumlah 67 siswa didistribusikan di dua kelas yaitu 33 siswa kelas XI IPA 2 sebagai kelas eksperimen dan 34 siswa kelas XI IPA 3 sebagai kelas eksiting. Instrumen test keterampilan berpikir kritis menggunakan test essay. Perlakuan penelitian pada kelas eksperimen menggunakan modul berbasis inquiry lesson dan kelas eksiting menggunakan modul umum yang digunakan di sekolah. Analisis data menggunakan uji-t pada taraf signifiansi nilai p = 0,000 (p<0,05). Gap skor pra dan pasca tes adalah 20,99% kelas eksperimen sedangkan kelas eksiting 10,76%. Hasil penelitian disimpulkan bahwa pembelajaran menggunakan modul sistem imunitas berbasis inquiry lesson (IL) dalam proses pembelajaran sangat signifikan untuk memberdayakan keterampilan berpikir kritis siswa.Permalink/DOI:http://dx.doi.org/10.15408/es.v10i1.7259